2017
DOI: 10.1038/bjc.2017.108
|View full text |Cite
|
Sign up to set email alerts
|

Tumour invasiveness, the local and systemic environment and the basis of staging systems in colorectal cancer

Abstract: Background:The present study aimed to examine the relationship between tumour invasiveness (T stage), the local and systemic environment and cancer-specific survival (CSS) of patients with primary operable colorectal cancer.Methods:The tumour microenvironment was examined using measures of the inflammatory infiltrate (Klintrup-Makinen (KM) grade and Immunoscore), tumour stroma percentage (TSP) and tumour budding. The systemic inflammatory environment was examined using modified Glasgow Prognostic Score (mGPS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 42 publications
(57 reference statements)
1
38
1
Order By: Relevance
“…These two parameters can reflect the overall situation of tumor stroma. In addition, they were reported to provide prognostic values in colorectal cancers (17,18). Our results suggested that these two parameters had neither correlation with EFTS expression nor correlation with RFS and OS in these GC cases.…”
Section: Discussioncontrasting
confidence: 56%
“…These two parameters can reflect the overall situation of tumor stroma. In addition, they were reported to provide prognostic values in colorectal cancers (17,18). Our results suggested that these two parameters had neither correlation with EFTS expression nor correlation with RFS and OS in these GC cases.…”
Section: Discussioncontrasting
confidence: 56%
“…After revision, 16 of these 24 papers were excluded for following reasons: eight studies did not provide HRs or CIs, seven studies were reviews, and one study was case report. Therefore, eight studies fulfilled our eligibility criteria for the analysis . Among them, one paper reported the results of two different population respectively, so it was treated as two studies for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, eight studies fulfilled our eligibility criteria for the analysis. 11,[21][22][23][24][25][26][27] Among them, one paper 24 reported the results of two different population respectively, so it was treated as two studies for analysis. Table 1 presented the characteristics of the eight included studies.…”
Section: Discussionmentioning
confidence: 99%
“…CIN accounts for a majority of the sporadic type of CRC [39], resulting in DNA aneuploidy and various mutations in proto-oncogenes and tumor-suppressor genes [40]. Mutations in tumor suppressors such as APC, SMAD4, and TP53—along with mutations in the proto-oncogene KRAS—are commonly identified in patients with CRC expressing CIN [41]. CIMP represents the global genome hypermethylation condition, resulting in the inactivation of several tumor suppressor genes or other tumor-related genes [37].…”
Section: The Rationale Of Using Msi and Mss Phenotype As A Predictivementioning
confidence: 99%